Sex differences in long-term effects of collagen-induced arthritis in middle-aged mice - Schuh, Bernhard Maximilian; Macáková, Kristína; Feješ, Andrej; Groß, Tim; Belvončíková, Paulína; Janko, Jakub; Juskanič, Dominik; Hollý, Samuel; Borbélyová, Veronika; Šteňová, Emőke; Pastorek, Michal; Vlková, Barbora; et al. (Frontiers in Physiology, 2023)
Introduction: Rheumatoid arthritis (RA) is a chronic inflammatory disorder with high prevalence among middle-aged women. Collagen-induced arthritis (CIA) is the most widely used animal model of RA, however, sex differences and long-term effects of CIA in mice are poorly described in the literature. Aim: Therefore, the present study aimed to analyze the long-term effects of CIA on the joints of middle-aged mice of both sexes and to describe potential sex differences. Materials and methods: CIA was induced in middle-aged DBA/1J mice by immunization with bovine type II collagen and complete Freund's adjuvant. Saline was administered to control mice. Arthritis score assessment, plethysmometry, and thermal imaging of the joints were performed weekly for 15 weeks. Locomotor activity, micro-computed tomography, joint histology and biochemical analyses were performed at the end of the experiment. Results: Our results indicate a similar prevalence of arthritis in both sexes of mice - 67% (8/12) of females and 89% (8/9) males with an earlier onset in males (day 14 vs. day 35). After the arthritis scores peaked on day 56 for males and day 63 for females, they steadily declined until the end of the experiment on day 105. A similar dynamics was observed in paw volume and temperature analyzing different aspects of joint inflammation. Long-term consequences including higher proteinuria (by 116%), loss of bone density (by 33.5%) and joint damage in terms of synovial hyperplasia as well as bone and cartilage erosions were more severe in CIA males compared to CIA females. There were no significant differences in locomotor activity between CIA mice and CTRL mice of any sex. Conclusion: This is the first study to describe the long-term effects of the CIA model in terms of sex differences in DBA/1J mice. Our results indicate sex differences in the dynamics, but not in the extent of arthritis. An earlier onset of arthritis and more severe consequences on joints, bones and kidneys were found in males. The underlying immune pathomechanisms responsible for the limited duration of the arthritis symptoms and the opposite sex difference in comparison to RA patients require further investigation.